Laser additive manufacturing method for low-stress, low-defect and low-deformation titanium alloy thin-wall part
By optimizing the laser additive manufacturing process parameters and post-introduction heat treatment measures, the problems of high residual stress, defects and deformation in titanium alloy printing are solved, and the forming quality is significantly improved.
Patent Information
- Application Number
- CN202411520243.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-14
AI Technical Summary
When printing titanium alloys, existing additive manufacturing technologies are prone to high residual stress, defects and deformation problems, which affect the forming quality.
By optimizing laser additive manufacturing process parameters, including laser power, scanning speed, interlayer deflection angle and island size, and introducing post-heat treatment measures, the residual stress of the forming parts is reduced and defects and deformation are reduced.
It significantly reduces residual stress during the printing process, reduces defects such as pores and cracks, controls the deformation of the forming parts, and improves the forming quality of titanium alloy parts such as TA15.
Smart Images

Figure CN119609152A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of additive manufacturing technology, and specifically discloses a low-stress, low-defect, and low-deformation additive manufacturing process for titanium alloys such as TA15. By optimizing key process parameters such as laser power, scanning speed, interlayer deflection angle, and island size, and introducing auxiliary measures such as post-heat treatment, the residual stress in the printing process is significantly reduced, defects such as pores and cracks are reduced, and the deformation of the formed parts is effectively controlled, thereby improving the forming quality of titanium alloy parts such as TA15. Background Art
[0002] Titanium alloys have high specific strength and high temperature stability and are widely used in complex load-bearing parts in aerospace, such as TA15 and other titanium alloys. Due to the high activity, deformation resistance and low thermal conductivity of titanium alloys, it is extremely difficult to manufacture complex thin-walled parts using traditional processes. Additive manufacturing technologies including Laser Powder Bed Fusion (L-PBF) provide a powerful means to break through the limitations of traditional processing methods and manufacture complex thin-walled titanium alloy parts due to their flexible processing and free design capabilities. Among them, L-PBF technology is also called selective laser melting (SLM) technology.
[0003] At present, domestic and foreign academic circles are relatively active in the research on selective laser melting of titanium alloys. The research on process parameters includes: laser input energy, substrate preheating status, etc., and a comprehensive study has been conducted on the mechanical properties, surface properties, biological properties, etc. of the formed samples; in addition, some scholars have also designed lightweight structures based on titanium alloys to enable them to be better used in the aerospace industry.
[0004] Bambach et al. (Bambach M, Sizova I, Szyndler J, et al. On the hot deformation behavior of Ti-6Al-4V made by additive manufacturing [J]. Journal of Materials Processing Technology, 2021, 288: 116840.) studied the difference between TC4 formed by directed energy deposition and selective laser melting, and studied the typical hot working conditions. The study found that when heated to the forming temperature, the martensite decomposed and produced an intermediate structure, which had better hot working properties than traditional forging materials. Zhang et al. (Zhang J, Liu Y, Bayat M, et al. Achieving high ductility in a selectively laser melted commercial pure-titanium via in-situ grain refinement [J]. Scripta Materialia, 2021, 191: 155-160.) achieved in-situ grain refinement of industrial pure titanium by regulating the forming process parameters. The results showed that higher input energy density is conducive to grain refinement. Du et al. (Du L, Qian G, Zheng L, et al. Influence of processing parameters of selective laser melting on high-cycle and very-high-cycle fatigue behavior of Ti-6Al4V[J]. Fatigue & Fracture of Engineering Materials & Structures, 2020, 44(1): 240-256.) studied the influence of L-PBF process parameters on the performance of L-PBF parts through orthogonal experiments. The results showed that porosity has a great influence on fatigue strength: the group with the smallest porosity has the highest fatigue strength in HCF and VHCF states.Issariyapat et al. (Issariyapat A,Visuttipitu P,Umeda J,etal.Refined grain formation behavior and strengthening mechanism ofα-titaniumwith nitrogen fabricated by selective laser melting[J].AdditiveManufacturing,2020,36:101537.) used additive manufacturing to prepare α-titanium alloy with high tensile strength and good elongation. By changing the scanning parameters, the mechanical properties were evaluated from the aspects of nitrogen content, energy density and other related aspects. The results show that with the increase of nitrogen content in the prepared titanium material, the tensile strength and hardness of the material are significantly improved. Ran et al. (Ran J, Sun X, Wei S, et al. Achieving Ti-5Al-4Sn-2Zr-1Mo-0.25Si-1Nb alloys with high strength and moderate ductility through selective laser melting [J]. Materials, 2020, 13 (23): 5527) studied the effect of laser power on the microstructure and mechanical behavior of titanium alloys, and studied the change in average grain size with increasing laser power. The concentration of aluminum inside the grain is higher than that near the grain boundary. The fracture analysis results show that cleavage fracture occurs in the L-PBF formed specimens.
[0005] In addition, during L-PBF forming, due to the large temperature gradient, there is a large residual stress inside the material, and the toughness is poor. Under the influence of residual stress, cracks are prone to occur. Cracks are the most common and destructive defects in selective laser melting. Therefore, how to optimize SLM process parameters and reduce residual stress, defects and deformation of formed parts has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] The purpose of the present invention is to provide a titanium alloy additive manufacturing process with low stress, low defects and low deformation. By optimizing the laser additive manufacturing process parameters, the residual stress of the formed parts can be significantly reduced, the defect formation can be reduced, and the deformation can be controlled, thereby improving the forming quality of titanium alloy parts such as TA15.
[0007] The technical solution adopted by the present invention is as follows:
[0008] A laser additive manufacturing method for titanium alloy thin-walled parts with low stress, low defects and low deformation adopts L-PBF process to form titanium alloy. By optimizing the laser power, scanning speed, interlayer deflection angle and island size in the forming process, the residual stress of the formed part is reduced and the forming quality is improved.
[0009] Furthermore, the titanium alloy is TA15 titanium alloy.
[0010] Furthermore, the parameters in the L-PBF process are set as follows to improve the forming quality: laser power is 250-310 W, scanning speed is 1000-1400 mm / s, scanning spacing is 100-200 μm, layer thickness is 20-50 μm, interlayer deflection angle is 67° or 90°, and island size is <10×10 mm.
[0011] Furthermore, the laser power is 280 W, the scanning speed is 1200 mm / s, the scanning interval is 140 μm, the layer thickness is 30 μm, the interlayer deflection angle is 67°, and the island size is 2×2 mm.
[0012] Furthermore, the parameters in the L-PBF process are set as follows to reduce the residual stress of the formed part: the body energy density is 40-60 J / mm 3 , the interlayer deflection angle is 67°, and the island size is <5*5mm.
[0013] Furthermore, the body energy density is 42.5 J / mm 3 , the island size is 2*2mm.
[0014] Furthermore, the titanium alloy formed by the L-PBF process is heat treated to further reduce the residual stress.
[0015] Furthermore, the heat treatment temperature is 800-900° C. and the time is >0.5 hour.
[0016] Furthermore, the heat treatment is carried out at a temperature of 900° C. for a period of 1 to 4 hours.
[0017] The present invention also provides a titanium alloy thin-walled part with low stress, low defects and low deformation manufactured according to the above method.
[0018] The beneficial effects of the present invention are as follows:
[0019] The titanium alloy additive manufacturing process provided by the present invention can significantly reduce the residual stress of the formed parts, reduce defects such as pores and cracks, control the amount of warping deformation, and improve the surface finish and overall quality of the parts. In addition, the process also has the advantages of high forming efficiency and wide application range, and can be widely used in high-end equipment manufacturing in the fields of aerospace, energy, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of 6 scanning strategies.
[0021] Figure 2 This is a photo of the TA15 printed sample.
[0022] Figure 3 It is the variation trend of sample density with volume energy density and pore distribution diagram.
[0023] Figure 4 The effect of laser power on residual stress at different positions, where (a) is 1 mm from the edge, (b) is 25 mm from the edge, and (c) is 50 mm from the edge.
[0024] Figure 5 The effect of scanning speed on residual stress at different positions, where (a) is 1 mm from the edge, (b) is 25 mm from the edge, and (c) is 50 mm from the edge.
[0025] Figure 6 is the effect of interlayer deflection angle on residual stress at different positions, where (a) is 1 mm from the edge, (b) is 25 mm from the edge, and (c) is 50 mm from the edge.
[0026] Figure 7 is the effect of island size on residual stress, where (a) is 1 mm from the edge, (b) is 25 mm from the edge, and (c) is 50 mm from the edge.
[0027] Figure 8 Figure 2 is the residual stress distribution of TA15 titanium alloy at different heat treatment temperatures, where (a) is 1 mm from the edge and (b) is 25 mm from the edge.
[0028] Fig. 9 This is the residual stress distribution of TA15 titanium alloy under different holding times, where (a) is 1 mm from the edge and (b) is 25 mm from the edge. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below through specific embodiments and drawings.
[0030] The present invention systematically studies the influence of printing process parameters including laser power, scanning speed, interlayer deflection angle, island size and other scanning strategies on the microstructure, defects, residual stress and mechanical properties of L-PBF formed TA15 titanium alloy. By establishing the influence of printing strategy on the evolution of TA15 microstructure, establishing the additive manufacturing process map that affects residual stress, and establishing the law of changes in organizational structure, mechanical properties and subsequent heat treatment parameters, it provides a reference for parameter optimization and in-depth research of L-PBF formed TA15 specimens, which is conducive to meeting the requirements of lightweight aerospace and broadening its application in complex structural parts in the aerospace field.
[0031] 1. Forming TA15 titanium alloy using L-PBF process
[0032] The L-PBF equipment uses EOS M290, and the printing parameters are shown in Table 1. The laser power P ranges from 250 to 310 W, the scanning speed v ranges from 1000 to 1400 mm / s, the scanning spacing h and the powder layer thickness d remain unchanged at 140 μm and 30 μm respectively, and the substrate preheating temperature is 200 °C. In order to comprehensively consider the synergistic effects of different process parameters, the volume energy density Ψ is used as the only variable to discuss its influence on the sample forming quality, microstructure, residual stress and mechanical properties. The calculation formula of Ψ is:
[0033] Table 1. TA15 titanium alloy printing parameters
[0034]
[0035] The scanning strategies in Table 2 are shown in Figure 1 . Figure 1 The following are six different scanning strategies used to study the effects of different interlayer deflection angles and island sizes on forming quality and residual stress, where 2*2, 2*10, and 2*100 represent island sizes of 2×2mm, 2×10mm, and 2×100mm, respectively. An island refers to a single molten pool formed by laser melting powder. Figure 2 Shown are printed TA15 specimens with different process parameters and sizes. The sizes of the two specimens are 100×2×20mm and 30×5×20mm respectively. The purpose is to ensure that the measurement of residual stress is not affected by wire cutting and to maximize the use of samples for testing of microstructure and mechanical properties.
[0036] right Figure 1 The six scanning strategies in are described as follows:
[0037] Scanning strategy ①: island size is 2×100 mm, and the inter-slice deflection angle is 67°;
[0038] Scanning strategy ②: the island size is 2×100 mm, and the inter-slice deflection angle is 90°;
[0039] Scanning strategy ③: island size is 2×100 mm, inter-slice deflection angle is 0°;
[0040] Scanning strategy ④: island size is 2×10 mm, and the inter-slice deflection angle is 90°;
[0041] Scanning strategy ⑤: island size is 2×2 mm, and the inter-slice deflection angle is 67°;
[0042] Scanning strategy ⑥: The island size is 2×2 mm and the inter-slice deflection angle is 90°.
[0043] 2. Effect of volume energy density on forming quality (roughness, density, porosity and warpage)
[0044] Table 2 compares the roughness measurement results of TA15 titanium alloy with five different L-PBF forming parameters. At the same laser power (250W), increasing the scanning speed will significantly increase the roughness. When the scanning speed increases from 1000mm / s to 1400mm / s, the roughness increases from 23.287μm to 26.692μm. At the same scanning speed (1200mm / s), the surface roughness of the sample decreases first and then increases with increasing laser power, but the change is not very obvious. When the laser power is 280W, the surface roughness is the minimum of 25.913μm, and when the laser power is 310W, the surface roughness is the maximum of 27.761μm. The scanning speed has a greater effect on the surface roughness than the laser power. The overall performance is that the roughness decreases first and then increases with the increase of the body energy density. When the laser power is 250W and the scanning speed is 1000mm / s, that is, the body energy density is 59.5J / mm 3 , with minimal roughness.
[0045] Table 2. Roughness test results of L-PBF formed TA15 at different volume energy densities
[0046] <![CDATA[Body energy density / J·mm -3 > Laser power / W <![CDATA[Scanning speed / mm·s -1 > <![CDATA[Surface roughness S a / μm]]> 42.5 250 1400 26.692 49.6 250 1200 26.312 55.6 280 1200 25.913 59.5 250 1000 23.287 61.5 310 1200 27.761
[0047] Figure 3 The green curve in the middle is the density of the L-PBF sample under different printing parameters measured by the Archimedean method. Factors such as the surface roughness of the sample and the open pores on the surface may affect the actual weight of the sample immersed in water, resulting in a higher measured value. At the same time, the metallographic method is also used to measure the percentage of pores in the total area of the polished cross section of the sample to represent the density, such as Figure 3 The orange curve shows that the density results of the two measurement methods show that the measurement results of the metallographic method and the Archimedes method show the same trend, that is, the density increases first and then decreases with the increase of the volume energy density. -3 The optimum density is achieved.
[0048] Table 3 shows the porosity statistics of printed TA15 at different volume energy densities. Higher volume energy density can effectively reduce porosity and improve forming quality. In this study, with the increase of volume energy density, the porosity of L-PBF first decreases and then increases. The volume energy density is 55.6 J / mm 3 When the energy density is high, the defect ratio can be reduced to 0.03031%. This is because at a very high volume energy density, the melting process of the molten pool is unstable, and the evaporation of the liquid phase and the splashing of liquid particles may lead to the formation of defects. When the volume energy density is low, it may lead to the generation of unmelted particles. The change of porosity measured by CT with energy density is consistent with the change of density.
[0049] Table 3. Porosity statistics of L-PBF printed TA15 at different volume energy densities
[0050] <![CDATA[Ψ / J·mm -3 ]]> <![CDATA[Defect Volume / mm 3 ]]> Defect / Total Volume / % 42.5 0.017438 0.37024 49.6 0.008119 0.17239 55.6 0.001428 0.03031 59.5 0.002249 0.04777 61.5 0.004336 0.09206
[0051] The warpage results of the samples under different volume energy densities are shown in Table 4. In Table 4, Δx, Δy, and angle represent the difference between the highest point and the lowest point in the horizontal direction, the difference between the highest point and the lowest point in the vertical direction, and the angle between the line connecting the two points and the horizontal plane, respectively. With the increase of laser power and the decrease of scanning speed, the deformation degree of the sample increases. In general, the warpage increases with the increase of volume energy density.
[0052] Table 4. Warpage measurement results of L-PBF formed TA15 at different volume energy densities
[0053]
[0054] Table 5 shows the warpage measurement results of L-PBF formed TA15 under different scanning strategies. The warpage of strategy ① samples is much smaller than that of strategies ② and ③. When the interlayer deflection angle is 0°, the scanning directions of each layer are parallel to each other, and the superposition effect of the consistent shrinkage of each layer makes the formed part more prone to warpage. For the scanning strategy with an interlayer deflection angle of 67°, the shrinkage directions of each adjacent layer are inconsistent, and there is no superposition effect, so the warpage will be reduced.
[0055] Table 5. Warpage measurement results of L-PBF formed TA15 under different scanning strategies
[0056] Scanning strategy Δx / μm Δy / μm tan angle / ° ① 16515.2 150.2 0.0091 0.5210 ② 13065.6 184.25 0.0141 0.8079 ③ 15865.6 262.25 0.0165 0.9470 ④ 8464 139.71 0.0165 0.9456 ⑤ 15385.6 137.57 0.0089 0.5122 ⑥ 8240 128.47 0.0156 0.8932
[0057] 3. Effect of L-PBF process parameters on residual stress
[0058] Figure 4The effect of laser power on residual stress at different positions is shown. When the laser power is constant, there is no obvious distribution pattern of residual stress in the growth direction, but as the laser power increases, the average residual stress gradually increases. This is because in the additive manufacturing process, the increase in laser power will cause the material to melt and solidify more quickly, resulting in a larger temperature gradient in the component, thereby causing high residual stress.
[0059] Figure 5 The effect of scanning speed on the residual stress at different positions is demonstrated. Analysis shows that with the increase of scanning speed, the average residual stress gradually decreases. This is because during the L-PBF forming process, the increase in scanning speed reduces the depth of the molten pool, while its length increases, and the accumulation of stress at the same position decreases.
[0060] Both the increase of laser power and the decrease of scanning speed can lead to an increase of residual stress, which generally increases with the increase of volume energy density. The higher the volume energy density, the smaller the lath width, and the stronger intergranular stress exists between the extremely thin laths, which will increase the residual stress to a certain extent; the proportion of large-angle grain boundaries also increases with the increase of volume energy density. Compared with small-angle grain boundaries, large-angle grain boundaries usually have higher dislocation transfer resistance, resulting in discontinuity of stress propagation path, more obvious dislocation accumulation and stress concentration, and thus an increase of residual stress.
[0061] Figure 6 The effect of the interlayer deflection angle on the residual stress at different positions is shown. As the interlayer deflection angle increases, the residual stress also increases. This is because the interlayer deflection angle fixed in a certain direction will increase the deformation after cooling and increase the probability of defects inside the material, such as pores and cracks, which will also increase the residual stress of the material. When the interlayer deflection angle is 0°, the printing direction is always along the same straight line, causing the residual stress to increase in the same direction; similarly, when the interlayer deflection angle is 90°, the residual stress has only two orientations; when the interlayer deflection angle is 67°, as the layer thickness increases, the printing direction coverage also increases, making the residual stress more evenly distributed in all directions to reduce the superposition of residual stress.
[0062] Island size is another factor to consider in L-PBF forming. It affects the various properties and residual stress of the sample and is an important indicator for optimizing the printing process and sample quality. It directly affects the mechanical properties of the component, such as strength, hardness, and toughness. Different island sizes will affect the internal stress distribution of the component, thereby affecting the mechanical performance of the component. Reasonable selection of island size can reduce the accumulation of residual stress and ensure the stability and durability of the component.
[0063] like Figure 7As shown in the figure, when the island size is 2*10, the residual stress value is significantly higher than that of the samples with island sizes of 2*100 and 2*2. There is close contact between the printed islands. Smaller islands will reduce the temperature gradient inside the sample. The smaller the deformation that may be experienced during the L-PBF forming process, the more uniform the internal structure and stress distribution will be, and the smaller the residual stress generated; while larger islands are more affected by thermal shrinkage during the cooling stage, and their internal residual stress may be greater. However, when the islands are too large, there is no mutual constraint between the islands, and the thermal stress and temperature gradient between adjacent islands change less, which can reduce the transfer of thermal stress between different islands, thereby reducing the accumulation of residual stress. At the same time, an island that is too large may result in more time for cooling, giving the material more time to release stress.
[0064] 4. Effect of post-heat treatment system on residual stress
[0065] Although in theory, the residual stress can be further relieved with the increase of heat treatment temperature, the growth of grains and phase change will cause the structure and performance of the material to change. Therefore, a reasonable post-heat treatment temperature will directly affect the stress relief effect of the material. In order to more clearly observe the effect of the heat treatment system on the residual stress, this embodiment selects two groups of samples with the largest residual stress in the printed samples and heat treats them.
[0066] from Figure 8 It can be seen that when annealing below the phase transformation point, the residual stress of the sample at 1mm and 25mm from the edge both dropped significantly, and the fluctuation amplitude decreased. When the sample was heat treated in the range of 800-900℃, the residual stress of the formed sample gradually decreased with the increase of annealing temperature. This is because the difference in residual stress after heat treatment at 800℃, 850℃ and 900℃ mainly comes from the change in the content of β phase in the organization. The proportion of β phase in the sample at the three heat treatment temperatures is different, so in the subsequent cooling process, the amount of high-temperature β phase transformed into α phase is also different. Although lattice distortion is inevitable in this process, the furnace cooling method has sufficient time to coordinate the changes in the microstructure. Heat treatment at 900℃ can reduce the residual stress of the sample to 27.1% and 18.5% of the average residual stress value of TA15 in the printed state.
[0067] When the heat treatment temperature reaches 950℃, the Widmanstatten structure is obtained. The residual stress is related to the β-phase content as well as the stress relaxation ability of different structures. The stress relaxation ability of the Widmanstatten structure at low temperature is stronger than that of the dual-state structure. There is no hindrance of the primary α phase during the phase change process. Therefore, the residual stress of the Widmanstatten structure after heat treatment at 950℃ is the lowest and the largest decrease, which is reduced to 17.2% and 9.2% of the average residual stress value of the printed TA15 at 1mm and 25mm from the edge, respectively.
[0068] from Fig. 9 It can be seen that when the heat treatment temperature is 900℃ for 1h, the residual stress has been reduced to 34.8% and 21.2% of the original printed samples. With the increase of the holding time, the residual stress becomes smaller and smaller. When the holding time is increased to 4h, the residual stress at different positions is reduced to 18.6% and 15.4% of the printed samples, respectively. This shows that increasing the holding time at high temperature can more effectively reduce the residual stress.
[0069] The above embodiment of the present invention successfully prepared several groups of TA15 titanium alloy specimens under different processes by using the selective laser melting forming technology, and studied the effects of process parameters and scanning strategies on forming quality, microstructure, residual stress and mechanical properties. The following conclusions were drawn:
[0070] (1) Both printing parameters and scanning strategies have a significant effect on the forming quality of the specimens. The roughness and porosity of the L-PBF formed TA15 titanium alloy specimens first decrease and then increase with the increase of the volume energy density, and the warpage gradually increases with the increase of the volume energy density. From the perspective of scanning strategy, the sample with the smallest roughness can be obtained when the interlayer deflection angle is 90° and the island is 2×2; the scanning strategy of 67° interlayer deflection angle and 2×2 small islands can make the warpage of the formed part smaller. Considering various indicators such as roughness, warpage and porosity, it is found that relatively good forming quality can be obtained when the laser power is 250-310W, the scanning speed is 1000-1400mm / s, the scanning spacing is 100-200μm, the layer thickness is 20-50μm, the interlayer deflection angle is 67° or 90°, and the island size is <10×10mm. Optimized parameters: laser power 280W, scanning speed 1200mm / s, scanning spacing 140μm, layer thickness 30μm, i.e., volume energy density 55.6J / mm 3 (Note: The above four parameters jointly determine the volume energy density), the interlayer deflection angle is 67° and the island size is 2×2 mm.
[0071] (2) The increase of laser power and the decrease of scanning speed will lead to the increase of residual stress. In general, the residual stress increases with the increase of volume energy density, and the volume energy density is 42.5J / mm 3 When the volume energy density increases to 61.5 J / mm 3 When the interlayer deflection angle is 0°, the average residual stress is the largest. From the perspective of scanning strategy, when the interlayer deflection angle is 0°, the residual stress of the sample is relatively the largest; the average residual stress of the interlayer deflection angle of 67° is relatively the smallest. The 2*100 sample, that is, the sample without distinguishing islands, has the smallest residual stress, but the average residual stress of the 2*10 island is much greater than that of the samples with 2*2 and 2*100 islands. Parameter range: Volume energy density is 40~60J / mm3 , interlayer deflection angle is 67°, island size is <5*5mm; the preferred parameters are body energy density 42.5J / mm 3 , interlayer deflection angle 67°, island size 2*2mm.
[0072] (3) Increasing the heat treatment temperature can make the material structure more uniform and enhance the effect of eliminating residual stress. The residual stress decreases with the increase of heat treatment temperature and holding time. The residual stress is relatively lowest after heat treatment at 950℃. The average residual stress at this temperature is reduced to 17.2% and 9.2% of the original sample, respectively. However, the sample undergoes phase change and the material structure changes, which affects other properties. When the heat treatment temperature is 900℃ below the phase change point, the residual stress decreases the most, and it decreases to 27.1% and 18.5% of the original sample at 1mm and 25mm from the edge, respectively. In addition, the residual stress decreases significantly with the increase of holding time, which shows that the increase of holding time at high temperature can also effectively reduce the residual stress. The parameter range for post-heat treatment to reduce residual stress is: temperature is 800-900℃, and time is >0.5 hours. The preferred parameters are: temperature is 900℃, and time is 1-4 hours.
[0073] The specific embodiments of the present invention disclosed above are intended to help understand the content of the present invention and implement it accordingly. It can be understood by those skilled in the art that various replacements, changes and modifications are possible without departing from the spirit and scope of the present invention. The present invention should not be limited to the contents disclosed in the embodiments of this specification, and the scope of protection of the present invention shall be subject to the scope defined in the claims.
Claims
1. A laser additive manufacturing method for titanium alloy thin-walled parts with low stress, low defects and low deformation, characterized in that: The L-PBF process is used to form titanium alloy. By optimizing the laser power, scanning speed, interlayer deflection angle and island size during the forming process, the residual stress of the formed part is reduced and the forming quality is improved.
2. The method according to claim 1, characterized in that The titanium alloy is TA15 titanium alloy.
3. The method according to claim 1, characterized in that The parameters in the L-PBF process are set as follows to improve the forming quality: laser power is 250-310 W, scanning speed is 1000-1400 mm / s, scanning spacing is 100-200 μm, layer thickness is 20-50 μm, interlayer deflection angle is 67° or 90°, and island size is <10×10 mm.
4. The method according to claim 3, characterized in that The laser power is 280 W, the scanning speed is 1200 mm / s, the scanning interval is 140 μm, the layer thickness is 30 μm, the interlayer deflection angle is 67°, and the island size is 2×2 mm.
5. The method according to claim 1, characterized in that The parameters in the L-PBF process are set as follows to reduce the residual stress of the formed part: the body energy density is 40-60 J / mm 3 , the interlayer deflection angle is 67°, and the island size is <5*5mm.
6. The method according to claim 5, characterized in that The volume energy density is 42.5 J / mm 3 , the island size is 2*2mm.
7. The method according to any one of claims 1 to 6, characterized in that: The titanium alloy formed by L-PBF process is heat treated to reduce residual stress.
8. The method according to claim 7, characterized in that The heat treatment temperature is 800-900° C. and the time is >0.5 hour.
9. The method according to claim 8, characterized in that The heat treatment is performed at a temperature of 900° C. for a time of 1 to 4 hours.
10. A titanium alloy thin-walled part with low stress, low defects and low deformation manufactured by the method according to any one of claims 1 to 9.
Citation Information
Cited By
A method and system for laser directed energy deposition manufacturing of thin-walled parts
CN122746482A